Core-Shell Structured PtxMoy@TiO2 Nanoparticles Synthesized by Reverse Microemulsion for Methanol Electrooxidation of Fuel Cells - Ai, Tianyu; Bao, Shuo; Lu, Jinlin (Frontiers in Chemistry, 2021)
The high price of catalyst and poor durability still restrict the development of fuel cells. In this work, core-shell structured PtxMoy@TiO2 nanoparticles with low Pt content are prepared by a reverse microemulsion method. The morphologies, particle size, structure and composition of PtxMoy@TiO2 nanoparticles are examined by several techniques such as X-ray Diffraction, X-ray photoelectron spectroscopy and transmission electron microscopy, etc. The PtxMoy@TiO2 electrocatalysts show significantly higher catalytic activity and better durability for methanol oxidation than the commercial Pt/C (ETEK). Compared to Pt/C catalyst, the enhancement of the electrochemical performance of PtxMoy@TiO2 electrocatalysts can be attributed to the core-shell structure and the shift of the d-band center of Pt atoms, which can weaken the adsorption strength towards CO molecules, facilitate the removal of the CO groups and improve electrocatalytic activity. The development of PtxMoy@TiO2 electrocatalysts is promising to reduce the use of noble metal Pt and has a great potential for application in fuel cells.